The Impact of Systemic Factors on Clinical Response to Ranibizumab for Diabetic Macular Edema - Singh, Rishi P; Habbu, Karishma; Ehlers, Justis P; Lansang, M Cecilia; Hill, Lauren; Stoilov, Ivaylo (Ophthalmology (Rochester, Minn.), 2016)
To evaluate the effect of systemic factors on best-corrected visual acuity (BCVA) achieved with ranibizumab (Lucentis; Genentech, Inc, South San Francisco, CA) for treatment of diabetic macular edema (DME) in the RIDE and RISE phase 3 studies. Exploratory, post hoc analysis of 2 randomized, double-masked, sham-injection controlled studies. Adults with DME, BCVA of 20/40 to 20/320 Snellen equivalent, and central foveal thickness of 275 μm or more. Analysis of RIDE (clinicaltrials.gov identifier, NCT00473382) and RISE (clinicaltrials.gov identifier, NCT00473330) pooled ranibizumab data through month 24. Change in BCVA was assessed for association with the following covariates: age, body mass index (BMI), blood pressure, serum glucose, glycosylated hemoglobin (HbA1c), blood urea nitrogen, serum creatinine, estimated glomerular filtration rate, and blood chemistry variables. Change in BCVA at month 24 was assessed according to the following categories of diabetes medication use history: insulin only (n = 193), insulin plus other medications (n = 221), or other noninsulin medications (n = 331). Change in BCVA from baseline assessed by randomized treatment group in pooled 0.3- and 0.5-mg monthly ranibizumab groups. In patients with DME, vision improvement with ranibizumab was not influenced by systemic factors such as diabetes medication history, serum glucose, HbA1c, renal function, BMI, and blood pressure. Patients taking insulin with or without other medications at baseline had longer diabetes disease duration (mean, 17.4 and 20.9 years, respectively) compared with those taking other noninsulin medications (mean, 11.9 years). At month 24, among ranibizumab-treated patients, the mean BCVA change from baseline (Early Treatment Diabetic Retinopathy Study letters ± standard deviation) was not different between patients taking only insulin (12.6±11.2 letters), insulin plus other medications (12.2±12.4 letters), or other noninsulin medications (14.0±13.7 letters). Mean BCVA change also was comparable among patients taking thiazolidinediones (12.9±9.7 letters) and those not taking thiazolidinediones (13.2±13.3 letters). There were no associations between systemic factors (baseline values or change from baseline) and mean change of BCVA at month 24. These results suggest that visual response to ranibizumab therapy in DME was not influenced by nonocular factors related to systemic management of diabetes in the RIDE and RISE studies.